2003
DOI: 10.1002/chem.200304769
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Bu2SnCl2‐Mediated Ring‐Opening Polymerization of ε‐Caprolactone by Multinuclear NMR Spectroscopy

Abstract: The ring-opening polymerization (ROP) of epsilon-caprolactone (CL) was carried out in toluene at 100 degrees C with n-propanol (nPrOH) in the presence of Bu(2)SnCl(2). It comes out that the molar mass of the polyester chains can be predicted from the initial monomer-to-alcohol molar ratio in accordance with a controlled ROP mechanism involving an O-acyl cleavage of the monomer to selectively form (alpha-propyloxy)(omega-hydroxy)poly(epsilon-caprolactone) chains. In order to gain fundamental understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 44 publications
0
25
1
Order By: Relevance
“…This result suggests that intramolecular transesterification, i.e. ''back-biting'', which causes degradation and formation of cyclic oligomers and consequently may cause a decrease of the molecular weight [31,32,33]. On the other hand, the monomer conversion increase with the time and it can be noted that initially the polymerization proceeds very slowly; this can be considered as an induction period (2 h), which consumed approximately 5 % of the monomer.…”
Section: Bulletin Of Chemical Reaction Engineering and Catalysis 9 (1)mentioning
confidence: 98%
“…This result suggests that intramolecular transesterification, i.e. ''back-biting'', which causes degradation and formation of cyclic oligomers and consequently may cause a decrease of the molecular weight [31,32,33]. On the other hand, the monomer conversion increase with the time and it can be noted that initially the polymerization proceeds very slowly; this can be considered as an induction period (2 h), which consumed approximately 5 % of the monomer.…”
Section: Bulletin Of Chemical Reaction Engineering and Catalysis 9 (1)mentioning
confidence: 98%
“…In the unused organotin derivatives (5, 6), the tin atom does not, of course, undergo coordination from the CDCl 3 NMR solvent molecules; in both cases, a rather broad 119 Sn resonance results at the well-known chemical shift of about 124 ppm, which is characteristic for nonpolar media (Figure 11, top). In a former study by our group with the homogenous organotin Bu 2 SnCl 2 catalyst, it was demonstrated [14] that in the presence of CL or PCL, a significant low-frequency shift is observed for the 119 Sn chemical shift of Bu 2 SnCl 2 , which is larger with CL than with PCL. This was explained by the fact that the monomer coordinates the tin atom more strongly than the polymer.…”
Section: Resultsmentioning
confidence: 93%
“…This was explained by the fact that the monomer coordinates the tin atom more strongly than the polymer. [14] Furthermore, the single 119 Sn resonance observed in both cases indicates fast exchange between noncomplexed Bu 2 SnCl 2 and tin di- Table 3). The white bar represents 500 mm.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The molecular weight increases with polymerization time and reaches a maximum after 6 h. The results show that between 3 and 8 h molecular weight increases gradually and after 10 h it decreases. This result suggests that intramolecular transesterification, i.e., "back-biting", which causes degradation and formation of cyclic oligomers and consequently may cause a decrease of the molecular weight [25][26][27], takes place. Maghnite-H + /ε-caprolactone weight ratio = 10%, reaction temperature 80 • C.…”
Section: Effect Of Maghnite-h + /Monomer Weight Ratiomentioning
confidence: 99%